Lack of MERS Coronavirus Neutralizing Antibodies in Humans, Eastern Province, Saudi Arabia - Gierer, Stefanie (Centers for Disease Control and Prevention, 2013)
We used a lentiviral vector bearing the viral spike protein to detect neutralizing antibodies against Middle East respiratory syndrome coronavirus (MERS-CoV) in persons from the Eastern Province of Saudi Arabia. None of the 268 samples tested displayed neutralizing activity, which suggests that MERS-CoV infections in humans are infrequent in this province.